2020
DOI: 10.1111/mpp.13006
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide alternative splicing profiling in the fungal plant pathogen Sclerotinia sclerotiorum during the colonization of diverse host families

Abstract: Sclerotinia sclerotiorum is a plant-parasitic fungus that causes white mould disease. It is known for its aggressive necrotrophic lifestyle, which means that the fungus actively kills the plant host cells and thrives by feeding on the dead plant material, and for exhibiting a broad host range. S. sclerotiorum can infect more than 600 host plants including economically important species such as tomato

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 80 publications
(126 reference statements)
2
16
0
Order By: Relevance
“…In muscle, brain, and gut, we also found several ASGs whose function may be involved in the cellular response to stresses (e.g., oxidative stress and DNA damage). Thus, our study supports that AS can act as an efficient mechanism in responding to environmental or cellular stresses, which has been extensively implicated in both animals and plants (Grantham & Brisson, 2018 ; Ibrahim et al., 2021 ; Kijewska et al., 2018 ). More importantly, our current study further indicates that AS may play a more important role than gene expression regulation in coping with the severe cellular stress in nature (see also Singh et al., 2017 ; Jacobs & Elmer, 2021 ; Martín et al., 2021 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In muscle, brain, and gut, we also found several ASGs whose function may be involved in the cellular response to stresses (e.g., oxidative stress and DNA damage). Thus, our study supports that AS can act as an efficient mechanism in responding to environmental or cellular stresses, which has been extensively implicated in both animals and plants (Grantham & Brisson, 2018 ; Ibrahim et al., 2021 ; Kijewska et al., 2018 ). More importantly, our current study further indicates that AS may play a more important role than gene expression regulation in coping with the severe cellular stress in nature (see also Singh et al., 2017 ; Jacobs & Elmer, 2021 ; Martín et al., 2021 ).…”
Section: Discussionsupporting
confidence: 85%
“…Mitochondrial dysfunction usually results in a decreased rate of ATP production and thus an increased rate of ROS generation, which will cause severe cellular stress (Ballard & Towarnicki, 2020 ; Ellison & Burton, 2006 ). Gene expression changes and alternative splicing (AS), acting as important transcriptional regulations, have been shown to play essential roles for cells and organisms in responding to environmental or cellular stresses efficiently (Ibrahim et al., 2021 ; Lee et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Isoforms merely expressed in planta by host-specific AS were identified in this phytopathogen. Thereby, colonization of diverse host families led to the accumulation of different transcripts and, consequently, altered protein domain structures, suggesting alternative functions of the isoforms during plant infection [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, a study of a few effector candidate genes suggested the existence of plant host-specific expression patterns (Guyon et al, 2014) and various small RNAs are differentially expressed on A. thaliana and common bean (Phaseolus vulgaris) (Derbyshire et al, 2019b). Furthermore, various isoforms originating from host-specific alternative splicing add additional plasticity to the transcriptomic profile of S. sclerotiorum (Ibrahim et al, 2020) and suggest polyspecialist adaptations in this species. Nevertheless, the extent to which the S. sclerotiorum genome harbors signatures of adaptation to a polyspecialist lifestyle has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…To test whether S. sclerotiorum activates distinct gene sets for the infection of diverse host species, we took advantage of transcriptomic expression data obtained from in vitro cultures of S. sclerotiorum and during infection of plants covering major botanical families in the Pentapetalae (Ibrahim et al, 2020; Peyraud et al, 2019; Sucher et al, 2020). We reveal a flexible, host-specific transcriptional program driven by core and host-response co-expression (SPREx) clusters.…”
Section: Introductionmentioning
confidence: 99%